2009
DOI: 10.1063/1.3124654
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal origin of electromigration at gold nanojunctions in the ballistic regime

Abstract: We have investigated the electromigration process at gold nanojunctions as small as several tens of atoms. Junction conductance showed successive drops by one conductance quantum, corresponding to one-by-one removal of gold atoms, only when the junction voltage exceeded certain critical values. The peak position in the histogram of the observed critical voltages agreed with the activation energies for surface diffusion of gold atoms. This fact indicates that the elementary process of electromigration in such s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 17 publications
3
76
1
Order By: Relevance
“…18,19,21,[23][24][25][26][27][28] In particular, the extent to which the electric field is screened from electromigrating atoms, and the role of external field inhomogeneities near an electromigrating atom both remain unresolved. 18,19,21,29,30 These questions remain unresolved, to a large extent, because the conventional separation of the EM force into electric field and electronwind components is somewhat artificial. 24 Meaning, local fields and currents are manifestations of the same nonequilibrium charge density and are therefore not readily decoupled as we demonstrate herein.…”
mentioning
confidence: 99%
“…18,19,21,[23][24][25][26][27][28] In particular, the extent to which the electric field is screened from electromigrating atoms, and the role of external field inhomogeneities near an electromigrating atom both remain unresolved. 18,19,21,29,30 These questions remain unresolved, to a large extent, because the conventional separation of the EM force into electric field and electronwind components is somewhat artificial. 24 Meaning, local fields and currents are manifestations of the same nonequilibrium charge density and are therefore not readily decoupled as we demonstrate herein.…”
mentioning
confidence: 99%
“…The critical bias voltages of electromigration in NCs of noble metals are 80-420 mV for Au and 240 mV for Cu. [37][38][39][40] These critical voltages are much higher than the bias voltage in this study (13 mV), and no electromigration was observed even in the surfaces of the Ag NW. The temperature of the Ag NW might increase owing to Joule heating during current passing, although the high current density originated from ballisticlike electron transport and the NC was connected to the microcantilever and millimeter-sized plate, which became large heat sinks, Note that lattice fringes were clearly observed on the Ag NC; no difference between the lattice images of the biased NCs and separated tips, i.e., bias-free states was observed.…”
Section: Conductance Measurement Of the Ag Ncsmentioning
confidence: 57%
“…Migration rates of more than one per second have already been experimentally observed. 22,31 Taking these observations into account, we can predict from the theoretical calculations that 3. ͑Color͒ The effective potentials around the migrating ͑a͒ gold and ͑b͒ sulfur atom at a bias of 0.2 V. In both cases, the migrating atom is placed at the position of the local minimum which appears on the right side in Figs. 2͑a͒ and 2͑b͒.…”
Section: B Electromigration Ratementioning
confidence: 96%
“…[10][11][12][13][14][15][16][17] Such nanogap electrodes can be used in various areas of nanotechnology such as a fabrication of single molecular devices in which an organic molecule is sandwiched between the electrodes. [18][19][20][21] More recently, in the fabrication of nanogap electrodes by the electromigrated break-junction technique, Umeno and Hirakawa 22 have observed an intriguing stepwise decrease over time of the electrical conductance of gold junctions. This behavior resulted from the disappearance of a conducting channel ͑6s orbital͒ of a gold atom at the junction and implied that the electromigration of single gold atoms takes place steadily at a threshold voltage ͑0.3-0.4 V͒.…”
Section: Introductionmentioning
confidence: 99%